Portfolio Optimization on Stocks from Agriculture, Finance, Mining, and Trade Sectors using Markowitz Method (The Indonesian Journal of Business Administration, 2022)
Abstract. The year of 2020 has become an unpleasant year for people around the world because of the COVID-19 virus outbreak. To minimize the outbreak, Indonesian government enforced lockdown, which resulted in the decrease of people’s purchasing power. This situation affecting the sales of many companies which resulted in many losses. It makes the economy falls and goes into recession. The fall of the economy also affecting the capital market, which has fallen into the lowest point in the last five years. In this situation, investors need to be careful in managing their investments, especially in equity investment, because equity market is strongly influenced by economic condition and market sentiment. One way to manage the investment is by analysing the portfolios’ composition that will give high return with minimum risk. The model that is commonly used for portfolio calculation is Markowitz method. This method aims to construct portfolio that will give certain return and know how much the risk is by doing diversification. Based on the industrial sector growth, there are four sectors that constantly growing more than Jakarta Composite Index (JKSE) in recent months. Those sectors are Agriculture, Finance, Mining, and Trade. The stocks will be selected from those four sectors. This final project uses daily adjusted closed price data on the Indonesia Stock Exchange downloaded from yahoo finance from January 2016 to April 2021. The portfolio is analysed using the Markowitz method. The Markowitz method produce an optimum portfolio with 54,81% annual return and 24,42% risk. This portfolio consists of 26,11% DEFI; 14,92% ZBRA; 12,21% ANTM; 8,95% WICO; 8,81% INDY; 8,54% BINA; 8,21% PTRO; 6,26% BBHI; and 6,00% KONI. The Net Asset Value from this portfolio is Rp10.745.Keywords: Investment, Portfolio, Return, Risk, Markowitz